Vascular health of fathers with history of intracytoplasmic sperm injection - Pengzhu Li; Magdalena Langer; Theresa Vilsmaier; Marie Kramer; Franziska Sciuk; Brenda Kolbinger; André Jakob; Nina Rogenhofer; Robert Dalla-Pozza; Christian Thaler; Nikolaus Alexander Haas; Felix Sebastian Oberhoffer (The Aging Male)
Objective Studies suggest that men who undergo assisted reproductive technologies (ART) may have a higher risk of cardiovascular disease; however, limited data on this matter is available. This observational pilot study aimed to investigate the overall vascular health of fathers with history of intracytoplasmic sperm injection (ICSI) compared to fathers whose partners conceived spontaneously.Methods Diet quality, physical activity, sedentary behavior as well as overall vascular function including the assessment of pulse wave analysis, intima-media thickness (cIMT), arterial stiffness of the common carotid artery (CCA) and blood lipids, were evaluated.Results A total of 34 fathers with history of ICSI and 29 controls (48.49 [46.32 − 57.09] years vs. 47.19 [40.62 − 55.18] years, p = 0.061) were included. After adjusting for age, no significantly increased cardiovascular risk was detected regarding vascular function.Conclusions The results suggest an unaltered cardiovascular risk profile in fathers with history of ICSI. In the future, prospective multicenter studies are required to validate these preliminary results.